The devil's pool and other stories - Sand, George, 1804-1876 (SUNY series, women writers in translation., 2004)
"Newly translated into English, "The Devil's Pool" is the most popular of George Sand's novellas and her best-selling work in France today. Illustrating Sand's brevity, liveliness, and exemplary storytelling, the tale deals with many of her characteristic themes - the relations between the sexes, the plight of the underprivileged, and the role of fantasy in human life - making it an ideal introduction to her work. Also included are translations of two of Sand's most admired short stories, "Lavinia" and "The Unknown God," as well as various relevant essays and documents."--Jacket